The Frequency of Maternal Complications after Home Delivered - Maryam Phulpoto, Aisha Kanwal, Roohi Nigar, Suhail Ahmed Bijarani, Ifat Baloch, Samiya Roshan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of maternal complications among women delivered at home by Traditional Birth Attended (TBA) Dais presenting at the emergency department of tertiary care hospital. Study Design: Descriptive case series Study setting: The study was conducted at the Emergency Department of Gynecology Unit –III of Liaquat University Hospital, Hyderabad. Study Duration: Six months from 1st May 2018 to 30th November 2018. Methods and Material: A sample of 140 was obtained, participants were selected by using the Non-probability sampling technique and all the women from 20 to 45 years of age either primipara or multiparous who delivered at home by traditional birth attendant (TBA) Dais and presented within 12 hours up to 10 days after delivery at emergency department of Gynecology Unit –III of Liaquat University Hospital, Hyderabad included, after getting informed and written consent from their family members, a questionnaire was used to collect information from the women or her relatives. Data was collected for the complications like post-partum hemorrhage, a retained product of conceptus, perpural sepsis perineal tears injuries. We have used SPSS version 20.0 software for both data entering and analysis. Frequencies and standard deviations were calculated and the chi-square test was used to analyse categorical variables. P values less than 0.05 were considered statistically significant. Result: The total number of women who delivered at home by (TBA’s)/ Dia’s and developed maternal complications presented in the emergency department within 12 hours up to 10 days during the study period was 140. The average age of the patients was SD 29.27±5.21 years. Regarding parity, 58(41.43%) were primigravida and 82(58.57%) multigravida. The postpartum hemorrhage was the commonest maternal complication observed in 62.14% (87/140) cases, retained placental products 27.14% (38/140), purpureal sepsis 7.86% (11/140) and perineal tear injuries 17.14% (24/140). Retained placental product, perianal tear injury and PPH were not statistically significant among different ethnicity while the rate of puerperal sepsis was statistically significant among different ethnicity groups. The frequency of PPH and perianal tear injury was significantly high among those women who had primigravida while the rate of Retained placental products and Puerperal sepsis was high in multigravida but it was not statistically significant. Conclusion: This study concluded that home deliveries conducted by untrained birth attendants were associated with increased maternal morbidity and a high risk of maternal mortality. The postpartum hemorrhage was the most common maternal complication observed in women after home delivery by a Traditional Birth Attended (TBA) Dais. Keywords: Home deliveries, Traditional birth attendant, maternal complication,